2016
DOI: 10.1155/2016/5797930
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Migration Inhibitory Factor and Malondialdehyde as Potential Predictors of Vascular Risk Complications in Type 2 Diabetes Mellitus: Cross-Sectional Case Control Study in Saudi Arabia

Abstract: Background. Malondialdehyde (MDA) has been implicated in the development of many acute inflammatory, autoimmune diseases as well as chronic inflammatory metabolic disorders. Involvement of inflammatory response and oxidative stress is currently suggested as a mechanism underlying development of diabetes and its complications. Objective. To evaluate the clinical utility of MDA, macrophage migration inhibitory factor (MIF), LDL-C/HDL-C, and TG/HDL-C ratio as noninvasive laboratory markers for prediction of T2DM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 47 publications
1
12
0
2
Order By: Relevance
“…It is also important to highlight that the levels of oxidative stress biomarkers in the entire cohort of T2DM patients did not significantly differ from those measured in the serum of healthy controls [35]. We demonstrated previously that significant differences in FRAP levels were seen between heathy controls and poorly controlled T2DM patients but not between heathy controls and T2DM patients with good glycemic control [36]; similarly, Morsi et al [37] did not find significant differences in malondialdehyde (MDA) levels between controls and well controlled T2DM patients. However, in heathy volunteers, Fpg sites, marker of oxidative damage, were reduced compared to well controlled T2DM patients [36].…”
Section: Discussionsupporting
confidence: 69%
“…It is also important to highlight that the levels of oxidative stress biomarkers in the entire cohort of T2DM patients did not significantly differ from those measured in the serum of healthy controls [35]. We demonstrated previously that significant differences in FRAP levels were seen between heathy controls and poorly controlled T2DM patients but not between heathy controls and T2DM patients with good glycemic control [36]; similarly, Morsi et al [37] did not find significant differences in malondialdehyde (MDA) levels between controls and well controlled T2DM patients. However, in heathy volunteers, Fpg sites, marker of oxidative damage, were reduced compared to well controlled T2DM patients [36].…”
Section: Discussionsupporting
confidence: 69%
“…MDA was also significantly increased in T2DM both with and without complications and performed better than ischemia-modified albumin (IMA), but it was of minor value compared to glycated haemoglobin (HbA1c) measurement in the evaluation of diabetes progression [65] (Table 2). T2DM patients with poor glycaemic control had significantly higher levels of MDA, when compared with the controlled T2DM patients and the control group [66, 67] (Tables 1 and 2). We also previously reported that circulating MDA was increased in poorly controlled T2DM with and without complications [63], and this effect was more pronounced in females [68]; however, other authors found no differences in MDA and isoprostanes between female T2DM patients with high or low HbA1c [69] (Table 2).…”
Section: Biomarkers Of Lipid Peroxidationmentioning
confidence: 99%
“…Furthermore, qualitative abnormalities of HDL-C are described; such as significant reduction in their antioxidative and endothelium-dependent vasorelaxant properties. 10 TGs are also affected in T2DM. Hypertriglyceridemia produces atherogenic, small, dense forms of LDL-C and decreases cholesterol transport to the liver by HDL-C.…”
Section: Introductionmentioning
confidence: 99%